BLENDED LEARNING APPROACHES IN TEACHING ENGLISH AT MILITARY ACADEMIC LYCEUMS - Dadaboyeva Fayyoza Khikmatulloyevna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article explores the application of blended learning models in teaching English at military academic lyceums. Combining traditional face-to-face instruction with digital tools, blended learning offers a flexible, learner-centered approach that is especially effective in structured and disciplined environments like military institutions. The article discusses the benefits, challenges, and best practices of implementing blended learning for English as a Second Language (ESL), highlighting its impact on language proficiency, learner autonomy, and operational communication skills. Emphasis is placed on the need for curriculum adaptation, teacher training, and integration of military-specific content within ESL instruction.